2015
DOI: 10.15376/biores.10.2.2526-2548
|View full text |Cite
|
Sign up to set email alerts
|

The Prospects of Rubberwood Biomass Energy Production in Malaysia

Abstract: Rubber has been shown to be one of the most important plantation crops in Malaysia, and rubber tree biomass has widespread applications in almost all sectors of the wood products manufacturing sector. Despite its abundance, the exploitation of rubberwood biomass for energy generation is limited when compared to other available biomass such as oil palm, rice husk, cocoa, sugarcane, coconut, and other wood residues. Furthermore, the use of biomass for energy generation is still in its early stages in Malaysia, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 52 publications
0
28
0
Order By: Relevance
“…To overcome the "waste-wood perception" of rubberwood, the government undertook concerted marketing efforts to boost the material's perception in the global market by rebranding and renaming it as "Malaysian Oak." Despite such extensive public-relation efforts, the success of rubberwood as a furniture material has been attributed primarily to its low cost and environmental friendliness (Ratnasingam et al 2012). Teoh et al (2011) reported that since the early 2000s, rubberwood-sawn timber enjoyed a strong demand in the domestic market and in the regional markets, while the supply of traditional wood resources from the natural forests reduced steadily.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome the "waste-wood perception" of rubberwood, the government undertook concerted marketing efforts to boost the material's perception in the global market by rebranding and renaming it as "Malaysian Oak." Despite such extensive public-relation efforts, the success of rubberwood as a furniture material has been attributed primarily to its low cost and environmental friendliness (Ratnasingam et al 2012). Teoh et al (2011) reported that since the early 2000s, rubberwood-sawn timber enjoyed a strong demand in the domestic market and in the regional markets, while the supply of traditional wood resources from the natural forests reduced steadily.…”
Section: Introductionmentioning
confidence: 99%
“…It is undeniable that the commercial exploitation of rubberwood in the wood-based industry has made significant socio-economic contributions to the country (Shigematsu et al 2011;Teoh et al 2011;Ratnasingam et al 2012). Although several studies have evaluated the socioeconomic perspectives of the rubberwood industry and the long-term economic potential of the tree crop to the Southeast Asian region, reports on the environmental value of rubberwood utilization are non-existent (Balsiger et al 2000;Norini et al 2009;Shigematsu et al 2011;Teoh et al 2011;Ratnasingam et al 2012;Noor Aini et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The increasing use of rubberwood (Hevea brasiliensis) as the primary raw material for furniture manufacturing, due to the reducing supply of wood from the natural forest, also had a positive impact on the industry (Menon 2000). Furniture made from rubberwood is widely accepted in the international market for its pleasant appearance, light colour, abundance, good machining properties, low cost, and renewable image (Ratnasingam et al 2015a). Its popularity is shown by its substantial export value; 80% of wooden furniture is made from this material.…”
Section: Introductionmentioning
confidence: 99%
“…Mill waste is infrequently used as an energy source in Malaysia, although many studies have shown that it is a promising source of biomass energy (Chuah et al 2006;Muis et al 2010;Mekhilef et al 2011;Shafie et al 2012;Mi and Han 2014;Noridah et al 2014;Ratnasingam et al 2015a). Furthermore, wood residue is a viable option for electricity generation (Muis et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation